WhatsApp-based intervention to promote tea consumption and healthy lifestyle in Indonesian’s adult - Briawan, Dodik; Sefrina, Linda Riski; Dewi, Mira; Rokhmah, Farida Dwi (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: Tea flavonoids have been shown to reduce Cardiovascular Disease (CVD) risks, and tea consumption might help reduce the problem in the community. Meanwhile, tea consumption among Indonesian people is still rare and in small quantities.Objectives: This research aimed to evaluate the effect of a WhatsApp-based education intervention, "HaH (Heart at Home)," a program that aims to increase KAP (Knowledge, Attitude, Practice) to prevent CVD by practicing a healthy lifestyle and encouraging tea consumption.Methods: Subjects were women/men who are married, members of IHF (Indonesia Heart Foundation), aged 25-50 years old, own and used a smartphone in their daily life. A total of 80 adults was participated in this study. The study design was pre-post intervention conducted online using WhatsApp for 21 days. The intervention included videos/ picture posts and online discussion through WhatsApp. Wilcoxon and McNemmar tests were used to examine the differences in subjects' KAP before and after the intervention.Results: Most subjects were women (96.3%) aged 25-40 years (78.8%) and housewives (67.5%). The knowledge score increased by about 17.5% (p<0.05). More than 10% of subjects increased their knowledge of CVD risk. Almost all subjects already had a positive attitude at baseline (94%) and was slightly increased to 97.0% (p<0.05). After the intervention, positive health practices such as exercise, consuming vegetables, relaxation, and sleep were increased. In contrast, harmful practices such as smoking, stress symptoms, and consuming high-cholesterol food were decreased.Conclusions: The present study showed that an online program effectively increases the KAP of subjects, although this can be maximized by having more interaction with subjects.